2014
DOI: 10.1038/cr.2014.165
|View full text |Cite
|
Sign up to set email alerts
|

The p53-induced lincRNA-p21 derails somatic cell reprogramming by sustaining H3K9me3 and CpG methylation at pluripotency gene promoters

Abstract: Recent studies have boosted our understanding of long noncoding RNAs (lncRNAs) in numerous biological processes, but few have examined their roles in somatic cell reprogramming. Through expression profiling and functional screening, we have identified that the large intergenic noncoding RNA p21 (lincRNA-p21) impairs reprogramming. Notably, lincRNA-p21 is induced by p53 but does not promote apoptosis or cell senescence in reprogramming. Instead, lincRNA-p21 associates with the H3K9 methyltransferase SETDB1 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
132
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(139 citation statements)
references
References 40 publications
4
132
0
2
Order By: Relevance
“…This is due to the fact that biochemical and in vitro studies have shown that hnRNP K has the capacity to regulate both tumor suppressive and oncogenic pathways, and both its overexpression and knockdown results in cell proliferation and apoptotic defects. [8][9][10][11][12][13] In support of its potential oncogenic functions, clinical association studies suggest that hnRNP K overexpression correlates with poor clinical outcomes and advanced disease status in a variety of malignancies, including melanoma, prostate, breast, lung, colorectal, hepatocellular, and esophageal cancers. [14][15][16][17][18] In contrast, other clinical studies suggest reduced hnRNP K expression, due to deletion of or mutations in the HNRNPK gene, may underpin the pathogenesis of acute myeloid leukemia (AML).…”
Section: Introductionmentioning
confidence: 99%
“…This is due to the fact that biochemical and in vitro studies have shown that hnRNP K has the capacity to regulate both tumor suppressive and oncogenic pathways, and both its overexpression and knockdown results in cell proliferation and apoptotic defects. [8][9][10][11][12][13] In support of its potential oncogenic functions, clinical association studies suggest that hnRNP K overexpression correlates with poor clinical outcomes and advanced disease status in a variety of malignancies, including melanoma, prostate, breast, lung, colorectal, hepatocellular, and esophageal cancers. [14][15][16][17][18] In contrast, other clinical studies suggest reduced hnRNP K expression, due to deletion of or mutations in the HNRNPK gene, may underpin the pathogenesis of acute myeloid leukemia (AML).…”
Section: Introductionmentioning
confidence: 99%
“…lncRNAs have dynamic effects in transcriptional regulation, and are involved in several human diseases, particularly cancer (52). For example, lincRNA-p21 prevents reprogramming by sustaining CpG methylation of pluripotency gene promoters (32). The present study investigated the potential roles of RP5-833A20.1 in methylation.…”
Section: Discussionmentioning
confidence: 99%
“…A B C during the development of disease (11,32,33). To assess the role of RP5-833A20.1 in the regulation of DNA methylation, the present study assessed the methylation level of the NFIA gene promoter using BSP.…”
mentioning
confidence: 99%
“…In iPSC, lincRNA‐p21 prevented reprogramming by activating epigenetic markers to induce heterochromatin at pluripotency gene promoters 80. Moreover, lincRNA‐p21 is down‐regulated in many types of cancer, including gliomas and GSCs, behaving as a tumour suppressor.…”
Section: Tumour‐suppressor Lncrnasmentioning
confidence: 99%